Effect of Traditional Cooking on Evaluation of Centella asiatica morphotypes for high yields of asiaticosidein Yellow-Fleshed Manihot esculenta - Dissanayake, T.D.C.K.; Abeysekera, A.M.; Salim, N.; Chandrika, U.G.; Padumadasa, C. (Journal of Pharmacognosy and Phytochemistry, 2016)
Attached

Centella asiatica (L) is a medicinal plant containing triterpenoid saponins including asiaticoside (ASTC) which currently incorporated on many cosmetic preparations. There are several morphotypes of the plant found in Sri Lanka. The ASTC content of five of the most common morphotypes were evaluated with the purpose of identifying a suitable morphotype for cultivation. A precise and accurate method based on HPLC analysis was developed. Of the five morphotypes studied, in field trials three were found to have significantly higher ASTC contents than the other two. Growing the same morphotypes in pots increased the ASTC content by nearly threefold.
Keywords: Centella asiatica; asiaticoside; HPLC; morphotypes; field trials